PERSUASIVE COMMUNICATION STRATEGIES IN ENVIRONMENTAL CAMPAIGNS: A COMPARATIVE STUDY OF THE BODY SHOP INDONESIA AND ECOTON FOUNDATION - Iqbal, Muhamad Iqbal; Prasetyo, Kurniawan (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
Indonesia is currently facing an unprecedented waste management emergency, with annual production reaching 69.7 million tons. This research provides a comprehensive analysis of the persuasive communication strategies utilized by two prominent yet distinct actors: The Body Shop Indonesia (commercial) and Ecoton Foundation (non-commercial). By employing a qualitative case study methodology, this study dissects digital narratives, symbolic messaging, and community engagement frameworks across multiple social media ecosystems. The findings reveal a dichotomy in persuasive approaches; The Body Shop employs "soft" persuasion integrating green marketing, celebrity ethos, and consumer rewards to cultivate sustainable lifestyle choices. In contrast, Ecoton utilizes "hard" persuasion grounded in scientific advocacy, visual pathos, and legal pressure to catalyze grassroots mobilization and systemic policy shifts. This expansion explores the implications of these strategies on public perception and behavioral change. The study concludes that the intersection of market-driven ethics and radical environmental advocacy is fundamental to mitigating Indonesia's plastic crisis and fostering long-term ecological resilience.